Estudo do processo fenton na remoção de digoxina e redução da toxicidade - Gubiani, Fábio Augusto (2019)
In this work the applicability of the Fenton process for the decontamination of synthetic effluent containing digoxin was investigated. For this, an analytical methodology was first developed and validated by high performance liquid chromatography using a diode arrangement detector with molecular absorption at 220 nm. This methodology proved to be applicable for the proposed purpose, since it was linear in the range of 0.1 to 10 mg L-1 and selective for digoxin in the presence of iron complexes, hydrogen peroxide and by-products of the union of these reagents. With this method, the stability of the drug was determined initially under conditions of acid (pH 3) and oxidative hydrolysis by oxidizing reagent (H2O2) and metal ions (Fe2+). Due to the stability of the tested conditions, the Fenton process was used for degradation of the drug, due to the fact that it presents physicochemical characteristics of bioaccumulation in living organisms. Experiments for the evaluation of the pH, [Fe2+] and [H2O2] variables were carried out under the conditions of: pH = 3, [Fe2+] = 30 mg L-1 and [H2O2] = 9990 mg L-1 degradation in 8 minutes. Studies using total organic carbon analysis showed mineralization of about 60% of the drug after 120 minutes of reaction. Residual hydrogen peroxide analysis showed 70% consumption of the inserted reagent after 120 minutes of reaction. And finally, toxicity tests demonstrated a reduction in toxicity due to the increase in LC50 for the simulated residue and after treatment by Fenton process, respectively.